Impact of green infrastructure in smart older adult care communities on the health of the older adult and the exploration of optimization paths - Wang, Zhuang; Gao, Lianping; Song, Peijuan (Frontiers in Public Health, 2025)
IntroductionThis study explores the multidimensional impacts of green infrastructure (GI) within smart older adult care communities on the physical health, psychological wellbeing, and social interactions of older adults. It further investigates optimization strategies for GI design to support healthy aging policies and enhance urban resilience.MethodsUsing longitudinal panel data from the China Health and Retirement Longitudinal Study (CHARLS, 2012-2020), the study applies panel regression models to examine the association between GI coverage and various health outcomes among older adults. Heterogeneity analysis assesses demographic-specific effects, and structural equation modeling (SEM) evaluates the mediating pathways through which GI influences public health.ResultsRegression results indicate that increased GI coverage significantly reduces the incidence of chronic and acute diseases (−0.34**), alleviates depression (−0.14), and anxiety (−0.12), and enhances subjective wellbeing (0.45) and frequency of social interactions (0.29**). Heterogeneity analysis reveals that health benefits are more pronounced among males and adults aged 70–79. SEM results show that GI indirectly mitigates the prevalence of COVID-19 by improving air quality (−0.15) and regulating ambient temperature (−0.10). Accessibility and equitable distribution of GI further amplify these positive effects.DiscussionThe findings underscore the critical role of GI as a public health intervention in smart older adult care communities. By integrating environmental health mechanisms with smart technologies, the study offers actionable recommendations for optimizing GI design-such as improving spatial equity, connectivity, and microclimate resilience. These insights contribute to the development of age–friendly urban planning frameworks and enhanced pandemic preparedness strategies. The study advocates for policies prioritizing high-quality, accessible green spaces to promote health, advance social equity, and address climate adaptation challenges.